Understanding language policy as a tool for access and social inclusion in South African higher education: A critical policy analysis perspective - Cele, N. (South African Journal of Higher Education, 2021)
This article argues that the development of language policy for transformation and social inclusion has significantly failed to achieve the ideal order of things given lack of robust monitoring and systematic implementation. This article uses a framework for policy analysis to reflect on the language policy in South African Universities. It explores reasons why the national language policy was introduced and uses the “effect and implementation” two-pronged framework to show how the national language policy has remained an instrument for the reinforcement of the supremacy of English as opposed to enhancing the development of African languages. The article further argues for the deliberate resourcing of the development of African languages to deal with language realities in South African universities. It asserts that the implementation of the South African national language policy framework is unmonitored and unresourced. It critiques the national language policy as political rhetorical and proposes a guiding framework for the development of African languages for meaningful us e in higher education as part of social inclusion. This article explored why the national language policy was established and why using the two-pronged policy analysis framework it can be argued that the policy has failed to have an effect impact on its aspirations and its implementation. A debate about the importance of African languages in teaching and learning, research, community engagement and organisational administration needs to become an integral part of the conversation on student-centeredness; improving graduation throughput; developing indigenous knowledge systems; improving research productivity; transformation and social inclusion; and social and cultural diversity at universities. These debates should be informed by newly developed knowledge frontiers on the role of African and indigenous languages in teaching and learning, and knowledge generation.